Myoxocephalus jaok - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Myoxocephalus jaok (Cuvier, 1829). Plain Sculpin . To 75 cm (29.5 in) TL (Spies et al. 2012). Seas of Japan and Okhotsk to western and eastern Bering Sea to western Beaufort Sea at least to 71°15’N, 153°07’W to eastern Aleutian Islands, and Limestone Inlet, south-eastern Alaska (Mecklenburg et al. 2016). Benthic; depth: intertidal to 680 m (2,231 ft) (min.: Mecklenburg et al. 2016; max.: Sheiko and Fedorov 2000). Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 123, DOI:10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008